Deferring Democracy : Promoting Openness in Authoritarian Regimes - Dalpino, Catharin E. (Book collections on Project MUSE., 2011)
The democratic surge in the past twenty years has led many Americans to assume that all societies are, or should be, making progress toward becoming practicing democracies. Many in the United States approach countries such as China, Iran, and Vietnam with impatience and bewilderment. These seemingly intransigent holdouts are the subject of intense policy debates, not in the least because they also play important roles in U.S. security and economic policy. This book takes a fresh look at the prospects for political change in these countries and argues that immediate opportunities exist to advan.